Analisis Pengaruh Pendapatan, Jumlah Anggota Keluarga dan Pendidikan Terhadap Jumlah Konsumsi Rumah Tangga Miskin Di Desa Batu Kandik Kecamatan Nusa Penida Kabupaten Klungkung - Vidiawan, Eka; Tisnawati, Ni Made (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2015)
The purpose of this study was to determine the effect of income, number of family members and education to total consumption of poor households in the village of Batu Kandik Klungkung District of Nusa Penida. This study uses quantitative research is to look at the amount of income, household size, education and the number of poor households consumption. This study uses 89 respondents poor households in the village of Batu Kandik Nusa Penida. Data analysis techniques used in this research is multiple linear regression. It was found that simultaneous income, number of family members and education have a significant effect on the pattern of consumption of the poor in the village of Batu Kandik, Kecamtan Nusa Penida Klungkung. Second, partial income, number of family members and education have a significant effect on the pattern of consumption of the poor in the village of Batu kandik Klungkung District of Nusa Penida.
Keywords: Revenue; Total Members Family; Education; Total Consumption